Drug-induced Steven Johnson syndrome - Sireesha, Vankodoth; Sultana, Asiya; Sri, P Ramya; Mateen, Ayesha; Rao, Tadikonda Rama (Indian Journal of Case Reports, 2025)
Adverse drug reactions (ADR) are a serious health issue. Drug hypersensitivity reactions can occur in a variety of illnesses, some of which are extremely serious. The skin is the site of the most frequent allergic reactions. Drugs (antimicrobials, such as penicillin and cephalosporins such as cefixime and non-steroidal anti-inflammatory drugs), infections, and other risk factors that have not yet been identified are the main causes of Stevens-Johnson syndrome (SJS). The skin is the site of the most frequent allergic reactions. Iatrogenic morbidity and mortality are largely caused by these reactions, which can range from minor itchy eruptions to potentially fatal situations. To improve the patient’s condition, the cause must be determined, the trigger must be removed, and supportive care must be provided. Mortality is high and rises with disease severity, patient age, and underlying medical conditions despite all therapeutic efforts. Survivors may experience chronic symptoms such as mucous membrane strictures and serious eye issues. This case reports that the patient was suffering from fever and conjunctivitis for the last 1 week with lesions on both lips, and ulcerations of the surface of the lips, tongue, and palate. The ulcers were hemorrhagic and tender on palpation. Hemorrhagic crusts and erosions were seen on both lips. The provisional diagnosis revealed that it is an acute febrile illness (AFI) with skin lesions with decreased evaluation further revealed it is an AFI with SJS secondary to drug reaction.